2022
DOI: 10.1097/01.aog.0000826724.49442.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Access to Hysterectomy within One Hospital System [A101]

Abstract: INTRODUCTION: Many patients receive an excess of opioids to treat their postoperative pain. We sought to assess the impact of a provider-based curricular intervention on postoperative prescribing patterns following benign obstetric and gynecologic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An institutional report on approximately 900 patients who underwent hysterectomy before and after the COVID-19 pandemic showed that the percentage of hysterectomies performed in White patients after the COVID-19 pandemic increased by 12%, whereas the number performed in Hispanic patients decreased by 13%. 28 Encouragingly, we found no racial or insurance-mediated disparities in the provision of hysterectomy during the COVID-19 surge.…”
mentioning
confidence: 52%
“…An institutional report on approximately 900 patients who underwent hysterectomy before and after the COVID-19 pandemic showed that the percentage of hysterectomies performed in White patients after the COVID-19 pandemic increased by 12%, whereas the number performed in Hispanic patients decreased by 13%. 28 Encouragingly, we found no racial or insurance-mediated disparities in the provision of hysterectomy during the COVID-19 surge.…”
mentioning
confidence: 52%